Ambient PM(2.5) exposure and rapid spread of COVID-19 in the United States - Chakrabarty, Rajan K. (Sci Total Environ, 2021)
It has been posited that populations being exposed to long-term air pollution are more susceptible to COVID-19. Evidence is emerging that long-term exposure to ambient PM(2.5) (particulate matter with aerodynamic diameter 2.5 μm or less) associates with higher COVID-19 mortality rates, but whether it also associates with the speed at which the disease is capable of spreading in a population is unknown. Here, we establish the association between long-term exposure to ambient PM(2.5) in the United States (US) and COVID-19 basic reproduction ratio R(0)– a dimensionless epidemic measure of the rapidity of disease spread through a population. We inferred state-level R(0) values using a state-of-the-art susceptible, exposed, infected, and recovered (SEIR) model initialized with COVID-19 epidemiological data corresponding to the period March 2–April 30. This period was characterized by a rapid surge in COVID-19 cases across the US states, implementation of strict social distancing measures, and a significant drop in outdoor air pollution. We find that an increase of 1 μg/m(3) in PM(2.5) levels below current national ambient air quality standards associates with an increase of 0.25 in R(0) (95% CI: 0.048–0.447). A 10% increase in secondary inorganic composition, sulfate-nitrate-ammonium, in PM(2.5) associates with ≈10% increase in R(0) by 0.22 (95% CI: 0.083–0.352), and presence of black carbon (soot) in the ambient environment moderates this relationship. We considered several potential confounding factors in our analysis, including gaseous air pollutants and socio-economical and meteorological conditions. Our results underscore two policy implications – first, regulatory standards need to be better guided by exploring the concentration-response relationships near the lower end of the PM(2.5) air quality distribution; and second, pollution regulations need to be continually enforced for combustion emissions that largely determine secondary inorganic aerosol formation.